2001
DOI: 10.1002/1096-8644(200101)114:1<18::aid-ajpa1002>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral proportions and admixture dynamics in geographically defined African Americans living in South Carolina

Abstract: We analyzed admixture in samples of six different African-American populations from South Carolina: Gullah-speaking Sea Islanders in coastal South Carolina, residents of four counties in the "Low Country" (Berkeley, Charleston, Colleton, and Dorchester), and persons living in the city of Columbia, located in central South Carolina. We used a battery of highly informative autosomal, mtDNA, and Y-chromosome markers. Two of the autosomal markers (FY and AT3) are linked and lie 22 cM apart on chromosome 1. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
149
2
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(179 citation statements)
references
References 27 publications
23
149
2
5
Order By: Relevance
“…The alleles in the category III histogram that occur at 20% or more in the European population and have an SFD value greater than 40% are likely to be ancestry informative and have been utilised in the following analyses (Figure 2). An SFD value of 40% excludes few taurine alleles and similar levels of frequency differential have been found to be useful in other studies (McKeigue, 1998;Parra et al, 2001).…”
Section: Selection Of Paasmentioning
confidence: 75%
“…The alleles in the category III histogram that occur at 20% or more in the European population and have an SFD value greater than 40% are likely to be ancestry informative and have been utilised in the following analyses (Figure 2). An SFD value of 40% excludes few taurine alleles and similar levels of frequency differential have been found to be useful in other studies (McKeigue, 1998;Parra et al, 2001).…”
Section: Selection Of Paasmentioning
confidence: 75%
“…In Brazil, for instance, the highest levels of European ancestry have been documented in the south of the country (the area of strongest European immigration during the "whitening" of Brazil), whereas the highest levels of African ancestry are in the northeast (historically the main area of African slave concentration) (72,82). Similarly, in US African Americans, African ancestry is highest in southern states, the area historically most strongly associated with slavery (9,19), and a south-to-north gradient of increasing European admixture has been interpreted as related to the northern migration of African Americans after the abolition of slavery (9,19,68,69).…”
Section: The Genetic Diversity Of the Americas Geographic Variation Imentioning
confidence: 99%
“…Finally, several communities tracing their ancestry to marooned slaves have been prime objects of study in multidisciplinary analyses examining the origin in Africa of the slaves who were transported to America (68,84,96). Genetic studies have shown that, although many of these populations have mainly African ancestry (8,68), some have substantial non-African admixture, indicating that contrary to what was previously thought, maroon settlements were not always that isolated (84).…”
Section: Special Populations In the Americasmentioning
confidence: 99%
“…The relatively low density of Native Americans coupled with the resistance of these population groups to Spanish acculturation and slavery led to the introduction of very large numbers of sub-Saharan Africans to the region. Although the demographic impact of Africans on the autochthonous population in other Latin American countries such as Colombia and Brazil was extremely high and still persists in modern populations (Alves-Silva et al 2000;Beleza et al 2005;Ely et al 2006;Parra et al 2001;Salas et al 2005b, c;, their real demographic impact in Argentina is a debatable topic. Some scholars maintain that a very significant number of African slaves were forcedly moved to Argentina, in particular to regions of intense agricultural activity: according to Victoria-Gomes (2002), in 1778 the population of Africans in Córdoba was *44%, whereas in 1887 the official percentage of Africans was reduced to *1.8%.…”
Section: Introductionmentioning
confidence: 99%